Impacts of continuing education on Primary Health Care professionals—A scoping review protocol - Laianny Krizia Maia Pereira; José Adailton da Silva; Ricardo A. de M. Valentim; Thaísa G. F. M. S. Lima; Nésio Fernandes de M. Junior; Alexandre R. Caitano; Tatyana Souza Rosendo (PLoS ONE, 2025)
Introduction Continuing Health Education is a strategy that integrates learning into the work process to transform health practices. Primary health care has proved to be a powerful space for consolidating continuing education, as it promotes reflection and learning based on the local singularities of the territory. Continuing health education is an important strategy for transforming the reality of Primary health care, reinventing work, and consequently changing practices. Objective This study aimed to identify and analyze the evidence regarding the impact of continuing education for health professionals in Primary Health Care in Brazil. Method This scoping review protocol that will be developed based on the Joanna Briggs Institute manual and guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews (PRISMA-ScR). The databases included in the study will be MEDLINE/Pubmed, Scielo, Lilacs, EMBASE, and Web of Science. Google Scholar will be used as gray literature. Studies published between 2007 and 2024 will be included, and no language restrictions will be applied. The Rayyan management software will be used as a tool to support the selection of studies. Two independent researchers will carry out a paired review to ensure the relevance of the studies. The studies will be analyzed descriptively, which will be guided by the categorization of results into three large groups: a) thematic areas covered; b) methodologies used; c) work process indicators and/or health results. Discussion Relevant aspects will be pointed out and interrelated in narrative form with the existing literature on the subject. Through the preparation of this protocol, it is aimed to identify to identify studies with evidence on the impact of continuing education in Primary Health Care in Brazil. This review could support the formulation of new professional training policies for PHC, contributing to the improvement of professional practices and the organization of work based on the needs of each territory.